Equity and trusts - Hudson, Alastair (Abingdon, Oxon [UK] : Routledge, 2013)
'Alastair Hudson's Equity and Trusts is an ideal textbook for undergraduate courses on the law of trusts and equitable remedies. It provides a clear, current and comprehensive account of the subject through which the author's enthusiasm and expertise shine through, helping to bring to life an area of the law which students often find challenging.Beginning with the core principles, Professor Hudson reinforces the key points by means of clear examples throughout each chapter, helping students to build and develop their own knowledge of equity and trusts. A set of lively, discursive essays reflecting on the law then begin to outline the broader political, social and economic context of the subject and encourage the reader to begin to engage with their own critical analysis. Although aimed at Students, Alastair Hudson is also the author of a practitioner text and brings that experience and detail to Equity and Trusts, which has now come to be cited in courts across different jurisdictions.The seventh edition is supported by a companion website which includes:over 50 short podcast lectures by the author discussing and clarifying key topics from within the book, which cover an entire course; a set of brief video documentaries filmed on location which provide context and bring to life selected key topics; a brief introductory video presentation from the author introducing the viewer to the subject of Equity and Trusts and to the book in particular'--
'Alastair Hudson's Equity and Trusts is an ideal textbook for undergraduate courses on the law of trusts and equitable remedies. It provides a clear, current and comprehensive account of the subject through which the author's enthusiasm and expertise shine through, helping to bring to life an area of the law which students often find challenging. Beginning with the core principles, Professor Hudson reinforces the key points by means of clear examples throughout each chapter, helping students to build and develop their own knowledge of equity and trusts. A set of lively, discursive essays reflecting on the law then begin to outline the broader political, social and economic context of the subject and encourage the reader to begin to engage with their own critical analysis. Although aimed at Students, Alastair Hudson is also the author of a practitioner text and brings that experience and detail to Equity and Trusts, which has now come to be cited in courts across different jurisdictions. The seventh edition is supported by a companion website which includes: over 50 short podcast lectures by the author discussing and clarifying key topics from within the book, which cover an entire course; a set of brief video documentaries filmed on location which provide context and bring to life selected key topics; a brief introductory video presentation from the author introducing the viewer to the subject of Equity and Trusts and to the book in particular'--
Includes bibliographical references (p. [1320]-1333) and index.
Keywords: Equity -- England; Trusts and trustees -- England